The Role of Reconstructive Surgery After Skeletal and Soft Tissue Sarcoma Resection. (June 2018) - Suresh, Visakha; Gao, Junheng; Jung, Sin-Ho; Brigman, Brian; Eward, William; Erdmann, Detlev
Abstract : Background: Skeletal and soft tissue reconstruction after sarcoma resection remains challenging. The use of advanced reconstructive techniques has been shown to improve function and increase rates of limb salvage. This study aims to analyze the utilization of plastic surgery within a multidisciplinary team approach after sarcoma resection at Duke University Medical Center from 2001 to 2014. Methods: Medical records were reviewed to determine procedure type, postoperative complications, and tumor recurrence. Observations were stratified by oncologic diagnosis, anatomic location, and procedure type. Patients were excluded if final pathology was not indicative of sarcoma, if resection or reconstruction was not performed at our institution, if resection preceded reconstruction by greater than 60 days, or if no follow-up was recorded within 3 months. Results: Of the 747 patients who met the inclusion criteria, 116 underwent reconstructive surgery. Tumor location was associated with a need for surgical reconstruction. Patients with upper ( P = 0.0073) or lower ( P = 0.0265) extremity tumors had a higher occurrence of plastic surgery involvement. Patients with a history of operative interventions had a higher likelihood of reconstructive surgery after oncologic resection (odds ratio, 1.649; P = 0.019). Neoadjuvant radiotherapy was associated with an increased likelihood of reconstructive plastic surgery after sarcoma resection (odds ratio, 2.131; P = 0.0004). Conclusions: Understanding the factors that necessitate reconstructive plastic surgery after sarcoma resection can enhance coordination of care within a multidisciplinary sarcoma center and leading to improved patient outcomes, including rates of limb salvage, as well as functionality and esthetic results.